HODGE, BOB y LOUIE, KAM (1998). The politics of Chinese language and culture. The art ofreading dragons. Londres: Routledge. 182 pp. ISBN 0-415-17266-7 - Fonte, Irene (Revista Latinoamericana de Estudios del Discurso, 2021)
HODGE, BOB y LOUIE, KAM (1998). The politics of Chinese language and culture. The art ofreading dragons. Londres: Routledge. 182 pp. ISBN 0-415-17266-7.